PEMBAHARUAN PEMIKIRAN DALAM ISLAM - Nur Alhidayahtillah (Lembaga penelitian dan Pengabdian kepada Masyrakat, 2018)
Renewal in Islam is different from Western renaissance. Renainsans emerged by getting rid of religion while Islamic renewal was the opposite. The renewal seeks to strengthen the principles and teachings of Islam to its adherents. The renewal of Islamic thought aims to influence and revive the principles of Islam that are neglected by its people. Muslims must rise from the lagging so far. Renewal in Islam is carried out by people who have an interest in their religion and fellow believers. Islam Renewal in Islam is useful to open the minds and insights of Muslims to be able to compensate for developments that are happening now without having to leave the teachings that already exist in his religion.